'I think my parents like me being bilingual': Cantonese–English DLBE upper elementary students mediating parental ideologies about multilingualism. Issue 6 (3rd July 2022) - Leung, Genevieve; Calcagno, Serena; Tong, Rosina; Uchikoshi, Yuuko
ABSTRACT : While the role of parental ideologies on children's bi/multilingual development and the role of children's beliefs about multilingualism are well-documented, less work examines how parental and student ideologies are enacted through talk. That is, how do students interpret what their family caregivers tell them about bi/multilingualism, and how do these beliefs about English and partner language(s) get enacted as a form of social personae? This article examines talk about language and identity from two focus groups with upper elementary students attending a Cantonese–English DLBE school. Participants frequently referenced their parents/caregivers in discussing goals and aspirations and likes/dislikes towards bi/multilingual language use through various forms of reported speech. These evaluations often took the form of commenting on 'good' and 'bad' language immersion curriculum and what a 'successful' or 'unsuccessful' bi/multilingual speaker should be like. A deeper discursive look into the utilitarian and intrinsic ideologies about multilingualism illustrates how this talk works in conjunction with neoliberal, classed ideas about linguistic knowledge and competitiveness. Findings demonstrate the complex ways learners see themselves in relation to broader perceptions of language learning and use and how DLBE is used as a vehicle towards (upper-middle) class orientations.